Internal competition in engineering educationa case study of project design competition in UNITEN - Chua Y.L.; Koh Y.Y. (American Scientific Publishers, 2023)
There are many approaches when it comes to achieving learning outcomes. One of the methods is project based learning. This research project studied from the perspective of students of a project design based module that is equipped with an internal design competition to enhance students learning outcome whilst making the learning process more attractive. The students were to work in groups and come up with a product design. At the end of the semester, the students will participate in the internal competition where they are to present their designed product to their peers and a panel of judges from the learned societies like IEM as well as academicians. After the internal competition, the students feedback are collected and analyzed and the results indicated that they are able to enhance not only their engineering skills such but also their soft skills such as presentation skills, communication skills, team work and independence. These skills are part of the learning outcome and are vital for future engineers. The experience accumulated will be beneficial in improving future classroom learning. Students feedback indicated that students gain more confidence and felt sense of accomplishment by participating in the internal competition. 2017 American Scientific Publishers All rights reserved.